2016
DOI: 10.1016/s1473-3099(15)00533-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of the mcr-1 colistin resistance gene

Abstract: Antimicrobials increase travelers' risk of colonization by extended-spectrum betalactamase-producing Enterobacteriaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
87
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(90 citation statements)
references
References 5 publications
2
87
0
1
Order By: Relevance
“…We were surprised to find that this new, emerging mobile ARG has been transferred to the healthy Chinese human gut microbiota through a potential food chain dissemination pathway (46), which is more likely the case for several other mobile ARGs that are shared between the animals and humans we observed in this study. In addition, mcr-1 is currently found in or circulated among E. coli, K. pneumoniae, and S. enterica, which supports our results that the mobile ARGs are exchanged most frequently among these three bacterial species ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…We were surprised to find that this new, emerging mobile ARG has been transferred to the healthy Chinese human gut microbiota through a potential food chain dissemination pathway (46), which is more likely the case for several other mobile ARGs that are shared between the animals and humans we observed in this study. In addition, mcr-1 is currently found in or circulated among E. coli, K. pneumoniae, and S. enterica, which supports our results that the mobile ARGs are exchanged most frequently among these three bacterial species ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Second, many of the mcr-1-positive isolates identified coharbor resistance determinants corresponding to specific antibiotics used in veterinary medicine, such as the floR gene encoding resistance to florfenicol (19). Many studies showed the wide dissemination of mcr-1-positive E. coli isolates, mostly in animals (14,23). Finally, the IncX4-type plasmids that are often identified as supporting the mcr-1 gene were identified in enterobacterial strains recovered from pigs, regardless of the presence of mcr-1 (24,25).…”
mentioning
confidence: 99%
“…Since the first report of plasmid pHNSHP45 carrying the mcr-1 gene (1), numerous retrospective studies have been performed worldwide to investigate the presence of this specific gene in strains isolated from environmental samples, food animals, food, and humans (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and the earliest evidence for its presence dates back to the 1980s (12). The mcr-1 gene was recently found to be carried by different plasmid replicon types, such as IncI2, IncHI2, IncP, IncFIP, and IncX4 (4,(13)(14)(15).…”
mentioning
confidence: 99%